Distribution of economically important weed species in the riparian and roadside vegetation of Serbia - Anđelković, Ana; Tmušić, Goran; Marisavljević, Dragana; Marković, Mladen; Cvijanović, Dušanka; Anačkov, Goran; Radulović, Snežana; Pavlović, Danijela (Acta herbologica, 2021)
Transportation corridors such as waterways and road networks serve as an entranceway for invasive and economically important weed species. The unstable environment of riparian areas and nutrient enrichment of road verges promotes the establishment and spread of these species, which may have a negative effect on nearby arable land, leading to severe yield reductions. We aimed to register the presence and frequency of five selected weed species (Chenopodium album, Cirsium arvense, Convolvulus arvensis, Cynodon dactylon, and Lactuca serriola) within these linear corridors. Sites along waterways were visited during 2013-2016, and road networks during 2018-2019. At each site, studied weed species were registered along 100 m transects, resulting in 250 localities along waterways and 180 near road networks. The most frequent species is Convolvulus arvensis, followed by Lactuca serriola and Chenopodium album, while less prevalent species are Cirsium arvense and Cynodon dactylon. The main characteristic of studied species is their preference for roadside habitats, except for Chenopodium album, which is more common in riparian areas.
Keywords: dispersal corridor; weeds; roads; waterways; Serbia